Experimental investigation on the feasibility and durability of a novel diesel particulate filter - Mohd Muhsein Taib, Mohd Muhsein (2012)
The increasing concerns on fuel prices, lowest fuel consumption, higher operating efficiency and low levels of carbon monoxide and unburned hydrocarbon during cold start have generated noticeable interest on diesel engine as a prime mover with expected higher soot and NOX emissions. In order to reduce the emission from diesel fuelled vehicle, some control technologies were introduced. One of the technology is diesel particulate filter (DPF) which consists of a porous substrate that permits exhaust to pass through but traps particulate matter (PM) or carboneous soot. Conventional DPFs are manufactured using expensive materials. In this study, alternative material based on alumina and zeolite was used to form porous ceramics filter installed in diesel fuelled vehicle exhaust system and named as novel diesel particulate filter (NDPF). The NDPF elements were arranged in line with 1cm spacing inside an enclosed casing. The NDPF showed potential as DPF to curb soot emissions. Pressure drop for the NDPF was in the range of 89% - 93% at every given flow rate during pressure drop test. Effective soot reduction was in the range of 60% - 70%. As predicted, trapped soot were accumulated mostly at the front and middle of NDPF. Scanning electron microscope (SEM) and energy dispersive xray (EDX) analysis confirmed the trapping ability of carbon elements in the range of 19% - 70% for each filter. Brake specific fuel consumption (BSFC) and brake mean effective pressure (BMEP) was slightly affected when NDPF was installed in the exhaust system and resulted to drops in engine efficiency in the range of 2% - 26%. Nevertheless, further reinforcement steps for the NDPF are needed to prolong its filtering capacity